PERANCANGAN SISTEM INFORMASI PERNIKAHAN DAN STATUS PERNIKAHAN KANTOR URUSAN AGAMA KECAMATAN CANDUANG AGAM BERBASIS WEB DENGAN FRAMEWORK CODEIGNITER - Miftahul Ilmi; Dharma Liza Said; Ahmaddul Hadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2016)
Chanduang’s Religious affairs office (KUA) is an institutionthat provide the service of marriage, reconciliations, and marriage’s consultations for Canduang’s sub district residents. In order to help Religious affairs office in registrations and data processing, an information system is needed to help this registration process can be done everywhere and without attending to the office. Moreover, for wide society, an application to show the information of Marriage’s status is also needed to avoid deception the status of Marriage.An Information System about marriage and marriage status  is designed in web-based with involve language programming HTML5, CSS3, JavaScript,Jquery and PHP5 with object oriented-based.  Meanwhile, the data base used is SQL. The design of the system also involves Use Case, Activity Diagram, Context Diagram, Flowchart, Class Diagram, Normalizes and ERD. This system also use the otherwise called in addressing with apply htaccess in the real file address as one of security System.This system information involves three users; Admin, officers andalso bridegrooms. The three levels of users are registered with private account to sign in to the system which has each username and password with MD5 encryption.  The main page of the systemwill show the information of Marriages’registrant and marriage schedule on Chanduang’s Religious affairs office. This system will help the KUA’s officer and also residents in applying marriage datas and show someone’s Marriage status. Key words: Information system, Marriage, Reconciliation, Web Programming